Mechanical and osmotic dehydration behavior of pineapple and retention of vitamin C - Jahan, Rownok; Islam, Md Ahmadul; Akter, Farzana; Alim, Md Abdul; Islam, Md. Nazrul (Fundamental and Applied Agriculture, 2019)
The study was designed to observe the behavior of mechanical and osmotic dehydration of pineapple, retention of vitamin C content during drying and development of jam from fresh and dehydrated pineapple. Osmotic dehydra- tion carried out with pineapples collected from local market of Mymensingh in July 2015 and found that pineapples contained higher moisture content (93.9%,wb) than normal (85-87%,wb) and showed contradictory osmotic behavior due to higher moisture content and hormonal effect. Then the stud- ies were conducted using pineapples of Gaint Kew variety collected from Madhupur without hormone treatment which contained 86.11% moisture, 0.36% ash, 13.89% total solid, 0.54% protein and 17.38 mg 100g−1 vitamin C. The osmotic concentration behavior was investigated using sugar and com- bined sugar-salt solution for 6mm thick pineapple slices and immersion time was 6 h. The extent of water loss, solid gain and normalized solid content were strongly influenced by strength of osmotic solution. It was found that K-value (mass transfer coefficient) increases with increasing concentration and was the highest (0.15 min−1) for 55/5% sugar/salt solution and lowest (0.07 min−1) for 45% sugar solution. Three different temperatures (55, 60 and 65 °C) and thicknesses (4, 6 and 8 mm) were used to investigate the drying behavior of pineapple slices in a mechanical dryer. Activation energy value of 8.14 Kcal g-mole−1 was found for fresh pineapple slices. 55/5% sugar/salt osmosed and dried pineapple gave 5.46 times higher dryer throughput com- pared to nonosmosed dried pineapple. Degradation of vitamin C content of pineapple at different air-dry bulb temperatures (55, 60 and 65 °C) of 6 mm thickness was investigated and activation energy for degradation of vitamin C was found to be 14.38 Kcal g-mole−1. Osmotic dehydration prior to air drying, gave the lower rate of degradation of vitamin C during drying compared to that dried without osmosis. Developed jams were tested for their acceptability by sensory evaluation using 1-9 point hedonic scale and jam made from osmotically dehydrated (55/5% sugar-salt and then dried at 60 °C) secured highest score (8.5) and ranked as ‘like very much’, while the other products were ranked as ‘like moderately’.